El desarrollo constitucional de los derechos indígenas en el Ecuador - Maldonado-Manzano, Rosa Leonor; Bravo-Urrutia, Stephanie; Bravo-Zapata, Jennifer Andrea; Sánchez-Guilindro, Lisbeth (IUSTITIA SOCIALIS, 2021)
El desarrollo constitucional de los derechos indígenas en el Ecuador